2016
DOI: 10.2174/1574892811666160128151437
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Caveolin-1 and E-Cadherin Correlates with the Clinicopathologic Features of Gastric Cancer and the EMT Process

Abstract: Decreased expression of Cav-1 and E-cadherin may play an important role in the progression of gastric cancer; Knockdown of Cav-1 may promote EMT of gastric cancer by targeting E-cadherin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The classical cadherin CDH1 (also known as E-Cadherin) is processed to generate a mature calcium-dependent cell-cell adhesion protein comprised of five extracellular cadherin repeats, a transmembrane region, and a highly conserved cytoplasmic tail. Decreased CDH1 expression is positively correlated with gastric cancer progression [25–27]; the decreased CDH1 (E-Cadherin) expression observed here might partially explain the ability of UBE2T knockdown to attenuate gastric tumor formation and growth. GSK3B (glycogen synthase kinase 3 beta) is a serine-threonine kinase involved in energy metabolism, neuronal cell development [28], inflammation, and osteoporosis [29] that also plays an important role in transcriptional regulation and oncogenic signaling.…”
Section: Discussionmentioning
confidence: 90%
“…The classical cadherin CDH1 (also known as E-Cadherin) is processed to generate a mature calcium-dependent cell-cell adhesion protein comprised of five extracellular cadherin repeats, a transmembrane region, and a highly conserved cytoplasmic tail. Decreased CDH1 expression is positively correlated with gastric cancer progression [25–27]; the decreased CDH1 (E-Cadherin) expression observed here might partially explain the ability of UBE2T knockdown to attenuate gastric tumor formation and growth. GSK3B (glycogen synthase kinase 3 beta) is a serine-threonine kinase involved in energy metabolism, neuronal cell development [28], inflammation, and osteoporosis [29] that also plays an important role in transcriptional regulation and oncogenic signaling.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have reported cross-talk between E-cadherin, Caveolin-1, β-catenin and TGF-β signaling [22][23][24][25][26]. Caveolin-1 protein is highly expressed in the K562-IR cell line when compared to K562.…”
Section: Tki-resistant K562-ir Cells Form Tumor Spheroids Express Himentioning
confidence: 99%
“…E-cadherin is the adhesion molecule of epithelial cell surface, and plays an important role in the adhesion between cells (33). The downregulation of E-cadherin is an important feature of EMT (34). Additionally, EMT is a significant cause of tumor invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%